2010
DOI: 10.1111/j.1439-0434.2010.01770.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a New Race of Sporisorium reilianum and Characterization of the Reaction of Sorghum Lines to Four Races of the Head Smut Pathogen

Abstract: Sporisorium reilianum is the causal agent of head smut on sorghum and maize. In order to effectively utilize host resistance to control this important disease in crops, it is necessary to monitor changes in disease dynamics and virulence of the pathogen. An outbreak of head smut was recently observed in a sorghum field, near Gaoping, Shanxi, China, and research was undertaken to characterize a putative new race of S. reilianum. A set of differential sorghum lines with resistance to several conventional races w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 5 publications
0
18
0
Order By: Relevance
“…Indira et al [4] identified 20 lines resistant to head smut including A7050, A232E, BICS 49, and Lian-Tang-Ai the Chinese pathotype 3. Further, PI961560 and SA281 were identified as resistant sources to all four Chinese head smut pathotypes [11]. In the United States, six converted sorghum accessions, including SC103-11E, SC155, SC166, and SC425 evaluated in Texas exhibited head smut resistance to pathotypes 1 to 4 [25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indira et al [4] identified 20 lines resistant to head smut including A7050, A232E, BICS 49, and Lian-Tang-Ai the Chinese pathotype 3. Further, PI961560 and SA281 were identified as resistant sources to all four Chinese head smut pathotypes [11]. In the United States, six converted sorghum accessions, including SC103-11E, SC155, SC166, and SC425 evaluated in Texas exhibited head smut resistance to pathotypes 1 to 4 [25].…”
Section: Resultsmentioning
confidence: 99%
“…Sorghum mono-cropping, planting susceptible hybrids, and the appearance of new virulent pathotypes in the United States (Table 1), China, and other sorghum growing regions have increased the incidence of head smut [3] [4] [6] [7] [8] [9] [10] [11]. In the 1990s, a head smut epiphytotic in China covered about 58 thousand hectares with an average incidence ranging from 18 to over 80% [4] [12].…”
Section: Introductionmentioning
confidence: 99%
“…Dodman and Obst (1985) reported race 3 of S. reilianum in Southeast Queensland, Australia. Recently, Zhang et al (2011) documented that there are four races found in the sorghum fi elds in China.…”
Section: Head Smutmentioning
confidence: 99%
“…Several good sources of resistance to head smut have been identifi ed and characterized (Peterson et al 2009;Zhang et al 2011). Some resistance sources have been utilized in various sorghum breeding programs (Rooney et al 2002;Zhang et al 2011).…”
Section: Head Smutmentioning
confidence: 99%
See 1 more Smart Citation